Safety Design for Space Systems - Sgobba, Tommaso; Sgobba, Tommaso; Musgrave, Gary Eugene; Johnson, Gary (Butterworth-Heinemann, 2023)
The lack of widespread education in space safety engineering and management has profound effects on project team effectiveness in integrating safety during design. On one side, it slows down the professional development of junior safety engineers, while on the other side it creates a sectarian attitude that isolates safety engineers from the rest of the project team. To speed up professional development, bridge the gap within the team, and prevent hampered communication and missed feedback, the entire project team needs to acquire and develop a shared culture of space safety principles and techniques.The second edition of Safety Design for Space Systems continues to address these issues with substantial updates to chapters such as battery safety, life support systems, robotic systems safety, and fire safety. This book also features new chapters on crew survivability design and nuclear space systems safety. Finally, the discussion of human rating concepts, safety-by-design principles, and safety management practices have also been revised and improved. With contributions from leading experts worldwide, this second edition represents an essential educational resource and reference tool for engineers and managers working on space projects. - Provides basic multidisciplinary knowledge on space systems safety design - Addresses how space safety engineering and management can be implemented in practice - Includes new chapters on crew survivability design and nuclear space systems safety - Fully revised and updated to reflect the latest developments in the field